Hypertrophic obstructive cardiomyopathy. Issue 10075 (25th March 2017) - Veselka, Josef; Anavekar, Nandan S; Charron, Philippe
Summary: Hypertrophic obstructive cardiomyopathy is an inherited myocardial disease defined by cardiac hypertrophy (wall thickness ≥15 mm) that is not explained by abnormal loading conditions, and left ventricular obstruction greater than or equal to 30 mm Hg. Typical symptoms include dyspnoea, chest pain, palpitations, and syncope. The diagnosis is usually suspected on clinical examination and confirmed by imaging. Some patients are at increased risk of sudden cardiac death, heart failure, and atrial fibrillation. Patients with an increased risk of sudden cardiac death undergo cardioverter-defibrillator implantation; in patients with severe symptoms related to ventricular obstruction, septal reduction therapy (myectomy or alcohol septal ablation) is recommended. Life-long anticoagulation is indicated after the first episode of atrial fibrillation.